PEMANFAATAN DATA MINING DENGAN METODE CLUSTERING UNTUK EVALUASI BIAYA DOKUMEN EKSPOR DI PT WINSTAR BATAM - Yuli Siyamto (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2017)
Data Mining is a technology that already exists and grows long enough. Many companies are less use of old data stored in the database, to be used as much as possible. This research is trying to apply Data Mining technology by using the clustering method to get new knowledge, which is expected to be useful for the continuity and development of the company. The algorithm used is K-Means Clustering which is the process of grouping a number of data or objects into a cluster (group) so that each cluster will contain data that is as similar as possible and different from other cluster objects. Tests were performed with the Rapid Miner 5.3 application. The result is clustered clustering customer data suggested for the evaluation of the cost of processing the export documents.